A step-economic and one-pot access to chiral Cα-tetrasubstituted α-amino acid derivatives via a bicyclic imidazole-catalyzed direct enantioselective C-acylation. Issue 18 (29th April 2020) - Wang, Mo; Zhou, Muxing; Zhang, Lu; Zhang, Zhenfeng; Zhang, Wanbin
Abstract : The first four-step sequential reaction for the synthesis of C α -tetrasubstituted chiral α-amino acid derivatives via auto-tandem catalysis has been developed. Abstract : C α -Tetrasubstituted α-amino acids are ubiquitous and unique structural units in bioactive natural products and pharmaceutical compounds. The asymmetric synthesis of these molecules has attracted a lot of attention, but a more efficient method is still greatly desired. Here we describe the first sequential four-step acylation reaction for the efficient synthesis of chiral C α -tetrasubstituted α-amino acid derivatives from simple N -acylated amino acids via an auto-tandem catalysis using a single nucleophilic catalyst. The synthetic efficiency is improved via a direct enantioselective C -acylation; the methodology affords the corresponding C α -tetrasubstituted α-amino acid derivatives with excellent enantioselectivities (up to 99% ee). This step-economic, one-pot, and auto-tandem strategy provides facile access to important chiral building blocks, such as peptides, serines, and oxazolines, which are often used in medicinal and synthetic chemistry.